The Reappearing Characters in Balzac's Comédie Humaine - Canfield, Arthur Graves, 1859-1947 (Studies in the Romance languages and literatures ;, 2019)
Balzac made a conscious effort in Comedie Humaine to multiply the reappearance, from book to book, of some of his characters. This careful analysis of nearly six-hundred reappearing characters shows that some appear only briefly, in no significant role; others play important parts; and some become principals in later action.